2009
DOI: 10.1128/aem.02753-08
|View full text |Cite
|
Sign up to set email alerts
|

Direct Expression of Antimicrobial Peptides in an Intact Form by a Translationally Coupled Two-Cistron Expression System

Abstract: We describe a novel prokaryotic expression system for the production of cationic antimicrobial peptides (AMPs). The method relies on a translationally coupled two-cistron system, in which the termination codon for the first cistron (which encodes the anionic polypeptide mIFc2, a derivative of human gamma interferon) overlaps with the initiation codon for the second cistron (which encodes a cationic AMP) in the sequence of 5-TAATG-3. By forming an insoluble complex with the AMP upon translation, the mIFc2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Our method results in a yield of bio-produced and purified pexiganan of around 1.6 mg from 800 mL bacterial cell culture (final cultivation OD 600 ~ 2), which accounts for 31% recovery of the theoretical yield of pexiganan. This recovery is twice the recovery obtained from the previous methods producing antimicrobial peptides which have similar physicochemical properties (Jang et al 2009). …”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our method results in a yield of bio-produced and purified pexiganan of around 1.6 mg from 800 mL bacterial cell culture (final cultivation OD 600 ~ 2), which accounts for 31% recovery of the theoretical yield of pexiganan. This recovery is twice the recovery obtained from the previous methods producing antimicrobial peptides which have similar physicochemical properties (Jang et al 2009). …”
Section: Introductionmentioning
confidence: 72%
“…This new downstream processing method is superior to traditional thermal purification methods in terms of yield and purity (Dwyer et al 2014; Zhao et al 2015), and more competitive than chromatographic methods in terms of production cost as compared to the previous purification processes of producing antimicrobial pexiganan peptide (Jang et al 2009). We expect that this new method could offer a cost-effective and high-yield approach which can be easily generalized and adapted to recover and purify other antimicrobial peptides from microbial cell factories.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the translation of an individual short peptide upstream of the gene utilizes the intrinsic helicase activities of ribosomes arriving at the second TIR, reducing the incidence of potentially inhibitory RNA structures and facilitating translation initiation at the second cistron [6,33]. When strong BEPs and MEPs were reused to express scFv, BEPs that performed well with EGFP also successfully expressed scFv, while two strong MEPs associated with the positive control failed to maintain their strong activities.…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al . succeeded in producing a potent antimicrobial peptide, buforin ІІb, by coexpression of human gamma interferon (Jang et al 2009). To obtain a large amount of ABF-2, we decided to apply this method to ABF-2 and examine the effects of aggregation-prone partner proteins in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, translationally coupled two-cistron plasmids were used to coexpress target peptides and partner proteins (Saito et al 1987; Jang et al 2009). However, genetic manipulation was needed to construct the translationally coupled two-cistron expression systems.…”
Section: Discussionmentioning
confidence: 99%